Effects of stocking density, energy and protein content on perfonnance of broiler chickens raised during late wet season (2016)
A 56-day feeding trial to investigate the effects of stocking density, energy and protein content on performance of broiler chickens during late wet season was carried out. In a 3 x 2 x 3 factorial arrangement using completely randomized design, six diets with three energy and two crude protein levels were formulated. Three stocking densities (birds/m2) of 10, 12 and 14 were used. A total of 576 one-week old Arbor Acre broilers chickens were assigned to the respective diets and stocking density, at 32 birds per treatment. Weight gain, feed intake, feed conversion ratio, survival rate, carcass yield, live weight/m2 and feed cost / live weight were assessed. Data were analyzed, using descriptive statistics and ANOVA α0.05. Energy x crude protein x stocking density interaction affects the feed intake (p<0.05) and the highest value was obtained using diet with low energy and crude protein levels. Treatment did not affect (p>0.05) survival rate, however, stocking density at 12 birds/m2 resulted in the best values (p<0.05) of weight gain (2230.71g) and feed conversion ratio (2.10) and the use of diets with lower crude protein and energy increased (p<0.05) the weight gain (2312.42g). The carcass yield was affected (p<0.05) by the interaction of energy x crude protein x stocking density, (p<0.05) with the lowest value (67.33%) found with birds raised on stocking density, 10 birds/m2 and diets with low crude protein and recommended energy. The lowest feed cost/live weight (p<0.05) was observed with stocking density at 12 birds/m2. Broiler chickens may be economically raised at stocking density 12 birds/m2 and on diet containing 2933kcal/kg ME with 21.92% crude protein for starter phase and 3095 kcal/kg ME and 19.14% crude protein for finishers during late wet season in Nigeria.